Oxidative Stress in Hypertensive Patients Induces an Increased Contractility in Vein Grafts Independent of Endothelial Function - Claudio Joo Turoni; Rodrigo Marañón; Maria Karbiner; Juan Muntaner; Víctor Proto; María Peral de Bruno (International Journal of Hypertension)
Objective. To evaluate the impact of oxidative stress on vascular reactivity to vasoconstrictors and on nitric oxide (NO) bioavailability in saphenous vein (SV) graft with endothelial dysfunction from hypertensive patients (HT). Methods. Endothelial function, vascular reactivity, oxidative state, nitrites and NO release were studied in isolated SV rings from HT and normotensive patients (NT). Only rings with endothelial dysfunction were used. Results. HT rings presented a hyperreactivity to vasoconstrictors that was reverted by diphenylene iodonium (DPI). In NT, no effect of DPI was obtained, but Nω-nitro-L-arginine methyl ester (L-NAME) increased the contractile response. NO was present in SV rings without endothelial function. Nitrites were higher in NT than in HT (1066.1 ± 86.3 pmol/mg; n=11 versus 487.8 ± 51.6; n=23; P<0.01) and inhibited by nNOS inhibitor. L-arginine reversed this effect. Antioxidant agents increased nitrites and NO contents only in HT. The anti-nNOS-stained area by immunohistochemistry was higher in NT than HT. HT showed an elevation of oxidative state. Conclusions. Extraendothelial NO counter-regulates contractility in SV. However, this action could be altered in hypertensive situations by an increased oxidative stress or a decreased ability of nNOS to produce NO. Further studies should be performed to evaluate the implication of these results in graft patency rates.